Advances in the study of gut microecology and mechanisms of hyperuricemia and gouty arthritis - Zhang, Youliang; Zhang, Hengyu; Miao, Tianwen; Wang, Xuetao; Zuo, Yanan; Zhang, Renwei; Zhang, Liangtong; Cheng, Yuan; Liu, Dong; Chen, Xin; Li, Longcan; Xie, Xingwen; et al. (Frontiers in Immunology, 2026)
Gouty arthritis is a metabolic disorder caused by purine metabolism dysregulation, characterized by monosodium urate crystal deposition in and around joints, triggering acute articular inflammation via NLRP3 inflammasome activation and IL-1β-mediated inflammatory cascades. While hyperuricemia represents a critical biochemical prerequisite for gouty arthritis development, elevated serum urate levels do not invariably lead to the disease. Mounting evidence suggests a significant relationship between gut microbiota and the pathogenesis of both gouty arthritis and hyperuricemia. The gut microbial ecosystem influences host health through metabolic and immune function modulation, performing essential roles in digestion, energy harvesting, and short-chain fatty acid production. Intestinal dysbiosis can damage epithelial integrity, compromise immune tolerance, and activate immune cells, thus contributing to disease onset and progression. Elucidating the complex interactions between gut microbiota and the mechanisms underlying gouty arthritis and hyperuricemia presents promising opportunities for developing novel preventative and therapeutic interventions. This review synthesizes recent advances in understanding the gut-joint axis and evaluates emerging therapeutic strategies including probiotics, dietary interventions, and fecal microbiota transplantation.